Adenosine A2A receptor plays an important role in radiation‐induced dermal injury. Issue 1 (28th September 2015) - Perez‐Aso, Miguel; Mediero, Aránzazu; Low, Yee Cheng; Levine, Jamie; Cronstein, Bruce N.
ABSTRACT: Ionizing radiation is a common therapeutic modality and following irradiation dermal changes, including fibrosis and atrophy, may lead to permanent changes. We have previously demonstrated that occupancy of A2A receptor (A2A R) stimulates collagen production, so we determined whether blockade or deletion of A2A R could prevent radiation‐induced fibrosis. After targeted irradiation (40 Gy) of the skin of wild‐type (WT) or A2A R knockout (A2ARKO) mice, the A2A R antagonist ZM241385 was applied daily for 28 d. In irradiated WT mice treated with the A2A R antagonist, there was a marked reduction in collagen content and skin thickness, and ZM241385 treatment reduced the number of myofibroblasts and angiogenesis. After irradiation, there is an increase in loosely packed collagen fibrils, which is significantly diminished by ZM241385. Irradiation also induced an increase in epidermal thickness, prevented by ZM241385, by increasing the number of proliferating keratinocytes. Similarly, in A2ARKO mice, the changes in collagen alignment, skin thickness, myofibroblast content, angiogenesis, and epidermal hyperplasia were markedly reduced following irradiation. Radiation‐induced changes in the dermis and epidermis were accompanied by an infiltrate of T cells, which was prevented in both ZM241385‐treated and A2ARKO mice. Radiation therapy is administered to a significant number of patients with cancer, and radiation reactions may limit this therapeutic modality. Our findings suggest that topical application of an A2A R antagonist prevents radiation dermatitis and may be useful in the prevention or amelioration of radiation changes in the skin.—Perez‐Aso, M., Mediero, A., Low, Y. C., Levine, J., Cronstein, B. N. Adenosine A2A receptor plays an important role in radiation‐induced dermal injury. FASEB J. 30, 457‐465 (2016). www.fasebj.org